2010
DOI: 10.1187/cbe.10-03-0020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interdisciplinary Undergraduate Research in Mathematics and Biology on the Development of a New Course Integrating Five STEM Disciplines

Abstract: Funded by innovative programs at the National Science Foundation and the Howard Hughes Medical Institute, University of Richmond faculty in biology, chemistry, mathematics, physics, and computer science teamed up to offer first- and second-year students the opportunity to contribute to vibrant, interdisciplinary research projects. The result was not only good science but also good science that motivated and informed course development. Here, we describe four recent undergraduate research projects involving stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 6 publications
(8 reference statements)
0
23
0
Order By: Relevance
“…Noteworthy examples are occurring in the USA, where science policy specifically encourages Higher Education Research & Development disciplinary integration (Caudill, Hill, Hoke, & Lipan, 2010). These relate to the greater integration of quantitative research skills into the other science disciplines.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Noteworthy examples are occurring in the USA, where science policy specifically encourages Higher Education Research & Development disciplinary integration (Caudill, Hill, Hoke, & Lipan, 2010). These relate to the greater integration of quantitative research skills into the other science disciplines.…”
mentioning
confidence: 98%
“…Legler et al (2010) report on an interdisciplinary undergraduate research program integrating statistics into a number of disciplines. Caudill et al (2010) report on the development of an undergraduate research program at the University of Richmond, funded by the Howard Hughes Medical Institute and the US National Science Foundation, which seeks to integrate biology, chemistry, physics, mathematics and computer sciences. Initially four undergraduate research projects were undertaken, which integrated various combinations of quantitative disciplines with the natural science disciplines.…”
mentioning
confidence: 99%
“…Our initial efforts involved a three-tiered approach to introducing students to relationships between pairs of disciplines: introductory courses, mid-to upper-division electives, and undergraduate research projects (Caudill, Hill, Hoke, & Lipan, 2010). At the introductory level, we made strides in three different areas.…”
mentioning
confidence: 99%
“…A comparison of pre-and postcourse scores from student surveys showed that post-course student comfort levels with several research-related tasks increased radically at both universities. All participating staff generally agreed that the methods and tools were valuable in this type of course and should be evaluated at other levels and areas of higher education, and shared in an expanded network of universities.In life science curricula, the integration of physical sciences, mathematics, and computer science has facilitated exciting results in device innovation, medicine, and biological research (National Research Council (NRC), 2003;Caudill et al, 2010). Human biology is a highly researchrelated, interdisciplinary area of life science studies.…”
mentioning
confidence: 99%
“…In life science curricula, the integration of physical sciences, mathematics, and computer science has facilitated exciting results in device innovation, medicine, and biological research (National Research Council (NRC), 2003;Caudill et al, 2010). Human biology is a highly researchrelated, interdisciplinary area of life science studies.…”
mentioning
confidence: 99%